Environmental Impact Assessment and Mitigation Measures of a Sand Mining Project - Gupta, Anamika (My University, 2018)
This report is made to put emphasis on Environmental Impact Assessment due to mining of mineral i.e. Sand which is a minor mineral. Mining at any place is done to fulfill the needs of the mankind. With the increasing modernization, for infrastructure development and construction of buildings, some minerals are required that can be used as a building raw material. Mining of minerals has positive as well as negative impacts also. Positive Impact is that it provides employment to the local people. But mining has some negative impact on environment. For evaluation of these impacts on environment, it is mandatory to get the Environment Clearance from the Authorities. To follow the proper procedure for predicting, analyzing and to overcome those impacts, there is a need to have a proper framework, which is said to be known as Environment Impact Assessment. There are number of ways in which an impact assessment can be done, but according to the need of the project, these methods are chosen so as to best describe the project. It is very important, to know the surrounding and exact location of the project sites for which we can use softwares like Google Earth, WR Plot etc. This report was basically based on predicting the major impacts and suggesting the corresponding mitigation measures. After analyzing the impact, these impacts were modeled on the software for the calculation of ground level concentration, so that the extent of the impact cam be evaluated. We can say that the allotted project has very limited impacts on the surrounding environment.
M tech thesis (Environmental Science and Technology)
Keywords: Sand mining; EIA; Impacts; WR Plot; Wind rose; GLC